Photonics Society of Poland celebrates 10th Anniversary - Woliński, Tomasz R. (Photonics Letters of Poland, 2018)
Photonics Society of Poland (PSP) celebrated its 10th Anniversary on 18 May 2018 in a beautiful historical Physics Building of the Warsaw University of Technology. The PSP Anniversary Symposium was co-located with the inaugural celebration in Poland of International Day of Light, that two days before - on 16 May 2018 - was inaugurated at the Headquarters of UNESCO in Paris.